Effect of a Herbal Formulation on Infection Prevention and Immune Regulation in Children with Frequent Relapse Nephrotic Syndrome - Wang, Haiyun; Tang, Binbin; Shi, Junjie; Wang, Yan; Wang, Qili (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: This study aims to investigate the effect of a herbal formulation "Guyuan Tang" on preventing the recurrence of children with frequent relapse nephrotic syndrome and its influence on immune function. Materials and Methods: In all, 30 children with frequent relapse nephrotic syndrome were randomly divided into the Traditional Chinese Medicine (TCM) group and the control group. The control group was treated with conventional western medicine, while the TCM group was treated with Guyuan Tang for three months based a control group. The changes in the immune function indices before and after treatment were compared between the two groups, and the frequencies of infection and recurrence were compared after 12 months of follow-up. Results: The level of IgG protein, the proportion of CD3+CD4+T cells, CD4/CD8 and Treg cells in the TCM group increased after three months of Guyuan Tang treatment (p < 0.05), which showed statistical differences compared with the control group (p < 0.05). After one year of follow-up, no statistically significant difference was observed in the incidences of recurrence and infection between the two groups (p > 0.05), but the hospitalization rate and the average number of infections in the TCM group were significantly lower than those in the control group (p < 0.05). Conclusion: Guyuan Tang could reduce the frequency of infection in children with frequent relapse nephrotic syndrome, and regulating the proportion of Treg cells, CD4/CD8 and IgG may be one of its mechanisms.
Keywords: Frequent relapse nephrotic syndrome; Infection; Traditional Chinese Medicine; Immune; Children